Bioengineered organotypic metastatic breast cancer mesenchymal stromal cell tumor models for drug screening - Lima, Hugo Macedo (2023)
Summary: Breast cancer (BC) is a highly aggressive and incurable disease in late stages of development. The tumor microenvironment (TME) in breast cancer is a master regulator of disease progression and dictates the clinical outcome in most of BC patients' interactions between the cellular and non-cellular components of the TME are now perceived as a crucial axis of tumor progression and drug resistance. Deepening our knowledge of BC ECM-TME interactions and of its cellular components can be crucial for discovering innovative therapeutic approaches. In this context, 3D in vitro tumor models capable of recapitulating extracellular matrix cues and the TME cellular landscape have unique potential for fundamental oncology research and new therapies preclinical screening. However, their high-throughput manufacture and high-cell density bioengineering have remained challenging. In this thesis a new bioengineered BC model based on breast-tissue specific decellularized matrix (dECM) was developed through the combinatorial application of superhydrophobic surfaces and photo crosslinking agents Ru/SPS to achieve spheroid-like cell densities within ECM enriched models. Moreover, the impact that the inclusion of cancer cells within this ECM mimetic environment has with and without varying populations of mesenchymal stem cells (e.g., derived from bone-marrow and adipose tissue) was studied, seeking to comprehend better how each population affects MDA-MB-231 cisplatin susceptibility and proving these platforms utility as both a study model and preclinical screening platform. In the end, a high cell density bead model with dECM and different cell cultures suitable for drug screening in Breast tumor context was produced. Using this ECM enriched models it was observed an increased resistance in stromal rich models to cisplatin, particularly noticeable when compared with dECM-free arrangements of the same populations. These results highlight the importance of developing 3D cancer models in a dECM-enriched setting, serving as platforms within which to further study the interactions present between tumor- associated mesenchymal stem cells and cancer cells, and therefore opening new pathways of research and therapy to be procured.